Cosmology: A Very Short Introduction - Coles, Peter (New York Oxford University Press, 2001)
Written in simple and accessible language, this non-technical introduction to cosmology, or the creation and development of the universe, explains the discipline, covers its history, details the latest developments, and explains what is known, what is believed, and what is purely speculative. In addition, the author discusses the development of the Big Bang theory, and more speculative modern issues like quantum cosmology, superstrings, and dark matter
Includes Index and Illustrations.
Keywords: Cosmology